2014
DOI: 10.1534/g3.113.008334
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of Contemporary Adaptation to Biotic Invasions: Quantitative Trait Locus Mapping of Beak Reduction in Soapberry Bugs

Abstract: Biological invasions can result in new selection pressures driven by the establishment of new biotic interactions. The response of exotic and native species to selection depends critically on the genetic architecture of ecologically relevant traits. In the Florida peninsula, the soapberry bug (Jadera haematoloma) has colonized the recently introduced Chinese flametree, Koelreuteria elegans, as a host plant. Driven by feeding efficiency, the populations associated with this new host have differentiated into a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…To test whether these changes were genetic or plastic, reciprocal rearing experiments were conducted that showed support for host-dependent genetic differentiation (Carroll et al 1997). More recently, QTL mapping has suggested that beak length in J. haematoloma may be controlled by a relatively small number of loci of moderate effect (Yu & Andr es 2014).…”
Section: Invertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether these changes were genetic or plastic, reciprocal rearing experiments were conducted that showed support for host-dependent genetic differentiation (Carroll et al 1997). More recently, QTL mapping has suggested that beak length in J. haematoloma may be controlled by a relatively small number of loci of moderate effect (Yu & Andr es 2014).…”
Section: Invertebratesmentioning
confidence: 99%
“…). More recently, QTL mapping has suggested that beak length in J. haematoloma may be controlled by a relatively small number of loci of moderate effect (Yu & Andrés ).…”
Section: From Phenotype To Genotypementioning
confidence: 99%